INFLUENCE OF GENDER AND RELIGION ON THE EXAMINATION STRESS OF SECONDARY SCHOOL STUDENTS IN SOUTH WESTERN NIGERIA - Adegboro, Joseph; Ajayi, N (European Journal of Health Sciences, 2020)
Background: Stress can raise the blood pressure of a subject and a number of environmental factors can change that level of the stress, especially the examination stress. These factors which include gender and religion are referred to as modifiers of stress. Objective: This study was therefore designed, using data of blood pressure, to understand the influence of religion and gender on the effect of examination stress on blood pressure of the secondary school students in South Western (SW) Nigeria. Methodology: The population of the study comprises all the students of Oroke Grammar School, Akungba Akoko (650) out of which a sample of 351 that satisfied our criteria was selected, using purposive sampling technique. Digital sphygmomanometer was used to measure the actual blood pressure readings of the respondents twice on each occasion and with at least thirty minutes interval in sitting positions. The measurements were carried out three times during the study, two weeks after resumption for the second term of the 2017/2018 academic year, two weeks before the second term examination and two weeks after resumption for the third term. Results: In this work, a rule of thumb was used to connect the perceived stress (PS) and the % change in the systolic blood pressure (SBP) when a subject is stressed, as PS=100/(% change in SBP). The results show that the group of female students in the general population always feels more stressed than their male counterpart, and respectively in the Islam religion and in the Christian religion always feels more stressed than their respective male counterparts. Also the groups of male and the female students in the Islam religion always feel more stressed than their groups of male and female students in the Christian religion Conclusion: Gender and religion were found to affect the level of perceived stress of the students. It was recommended that male students should be encouraged to go for regular blood pressure checkups as they are more likely not to feel stressed even when their blood pressure has increased much above the normal. This is one of the measurements the health personnel should do whenever a male student in particular is in the health centre. Because the number of Christian students in this work is much larger than the number of Muslim students, more research is needed with comparable number of students in each religious group to further understand how religious practices play a role in perceived stress of college students. Future research should include more variables that influence coping methods and parental influence and guidance.